Activities And Difficulties In Hybrid Listening Class Perceived By High And Low Achievers - Baso Jabu; Asriati Asriati (Seminar Nasional LP2M UNM, 2022)
Abstract. After the outbreak of Covid-19 pandemic, the educational sector is urged to change almost everything including the process of teaching and learning. One of the best solutions which is available is the use of hybrid class method. Therefore, this study means to find out the high achievers and low achievers’ perception on the activities and difficulties in hybrid listening class. The process of data gathering applied interview, questionnaire distribution, observation, and document review. There are 20 participants from English education students that contribute to this study which consists of 12 high achievers and 8 low achievers who are chosen purposively. The results show that there are several activities being used in hybrid listening which consist of main activities and extra activities. Both the high achievers and low achievers show positive attitude toward the activity used in hybrid listening class. While the obstacles they faced during the hybrid listening class is the LMS error and bad/insufficient internet connection. Key words: Activity, Hybrid Listening class, High and low achievers